PCDDs, PCDFs, PCBs and OCPs in sediments from selected areas in the Slovak Republic - Čonka, Kamil; Chovancová, Jana; Stachová Sejáková, Zuzana; Dömötörová, Milena; Fabišiková, Anna; Drobná, Beata; Kočan, Anton (Chemosphere, 2014)
Within our research project, 34 river bottom sediments were collected in 2006-2007 at five areas across Slovakia with industrial sources of persistent organic pollutants (Košice, Krompachy, Nemecká, Šala, Nováky) and one background area (Starina). Sediments were analyzed for seven 2,3,7,8-substituted polychlorinated dibenzo-p-dioxins (PCDDs) and 10 dibenzofurans (PCDFs), 12 dioxin-like and 6 indicator polychlorinated biphenyls (PCBs), hexachlorobenzene (HCB) and 1,1,1,-trichloro-2,2-bis(p-chlorophenyl)ethane (p,p'-DDT) with 1,1-dichloro-2,2-bis(p-chlorophenyl)ethylene (p,p'-DDE). Analytical procedure based on accelerated solvent extraction followed by a semi-automated clean-up and fractionation was used. Determination of target compounds was performed by HRGC-HRMS analysis. Total WHO toxic equivalent WHO1998-PCDD/F/dl-PCB-TEQ concentrations ranged from 0.26 to 559 pg TEQ g(-1) dry matter (dm), with a median 2.2 pg TEQ g(-1) dm. The sums of six indicator PCBs were in the range 0.56-1014 ng g(-1) dm, with a median 11.8 ng g(-1) dm. The concentrations of organochlorine pesticides HCB and p,p'-DDE/DDT varied from 0.15 to 34.8 ng g(-1) dm, with a median 0.91 ng g(-1) dm and 0.46-34.1 ng g(-1)dm, with a median 6.7 ng g(-1)dm, respectively. The most abundant congeners in all sediment samples among dioxins, furans and PCBs were OCDD, 1,2,3,4,6,7,8-HpCDF, PCB-118 and PCB-153.
Keywords: monitorování životního prostředí; hexachlorbenzen; polychlorované bifenyly; benzofurany; dichlordifenyldichlorethylen; Environmental Monitoring; Pesticides; Polychlorinated Dibenzodioxins; Geologic Sediments; řeky; Rivers; chemické látky znečišťující vodu; geologické sedimenty; Hexachlorobenzene; Polymers; Slovakia; Slovenská republika; Polychlorinated Biphenyls; Water Pollutants, Chemical; chlorované uhlovodíky; Dichlorodiphenyl Dichloroethylene; Hydrocarbons, Chlorinated; polychlorované dibenzodioxiny; pesticidy; Benzofurans; polymery